2019
DOI: 10.1186/s13020-019-0261-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional polysaccharides of carob fruit: a review

Abstract: Polysaccharides in carob fruit, including carob bean gum (also known as carob gum, locust bean gum) and carob fiber, are widely used in industries such as food, pharmaceuticals, paper, textile, oil well drilling and cosmetics. Carob bean gum is a galactomannan obtained from the seed endosperm of carob tree and the fiber is obtained by removing most of soluble carbohydrates in carob pulp by water extraction. Both the gum and fiber are beneficial to health for many diseases such as diabetes, bowel movements, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 85 publications
0
38
0
Order By: Relevance
“…Although carob pulp is reported to exert several biological effects mainly because of the presence of phenolic compounds [26,30]. In this study we have focused in analyzing the effects of supplementation with a carob pod and seeds extract, since it is reported that these parts contain higher amounts of galactomanns, gallic acid, and gallotannins and exert a stronger antioxidant capacity as well as anti-hypertensive effects in vitro [31].…”
Section: Introductionmentioning
confidence: 99%
“…Although carob pulp is reported to exert several biological effects mainly because of the presence of phenolic compounds [26,30]. In this study we have focused in analyzing the effects of supplementation with a carob pod and seeds extract, since it is reported that these parts contain higher amounts of galactomanns, gallic acid, and gallotannins and exert a stronger antioxidant capacity as well as anti-hypertensive effects in vitro [31].…”
Section: Introductionmentioning
confidence: 99%
“…This research contributes to authenticity of carobs, adding value to local products.Metabolites 2020, 10, 62 2 of 11 demands. Carob flesh is rich in minerals, dietary fibers, sugars, polyphenols, D-pinitol and with low fat content, whereas the seed is abundant with locust bean gum (E 410), a natural hydrocolloid widely used in the food industry [3][4][5][6][7]. The chemical composition of carob flesh is presented in Table 1; however, these values are affected by various practices and factors (e.g., farming, genotyping, climate, soil, etc.).…”
mentioning
confidence: 99%
“…Carob ( Ceratonia siliqua L.) is an evergreen tree widely cultivated in the Mediterranean area. It belongs to the Leguminosae family and its scientific name derives from the Greek word “ kera ”, due to the keratomorphic shape of the fruit, and the Latin word “ siliqua ”, related to the hardness and shape of the pods [ 1 , 2 ]. The carob fruit (bean) is called pod and consists of two parts: the seeds (10%) and the pulp (90%).…”
Section: Introductionmentioning
confidence: 99%